Encapsulating material for all-solid-state battery and all-solid-state battery using same
By using ionomers and anti-corrosion treatment layers in the packaging materials of all-solid lithium batteries, the problems of hydrogen sulfide leakage and current collector corrosion are solved, and the safety and life of the battery are improved, while simplifying the manufacturing process.
Patent Information
- Application Number
- CN202411951363.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-30
- Filing Date
- 2020-01-30
- Publication Date
- 2025-03-25
AI Technical Summary
When using sulfide-based solid electrolytes, existing all-solid lithium batteries have problems of hydrogen sulfide leakage and current collector corrosion, and the manufacturing process is complicated and the cost is high.
A sealant layer containing ionomers is used to react metal ions with hydrogen sulfide to make it harmless, and an anti-corrosion treatment layer is provided in the encapsulation material to prevent hydrogen sulfide from corroding the current collector.
Effectively prevent hydrogen sulfide leakage and current collector corrosion, improve battery safety and life, while simplifying the manufacturing process and reducing costs.
Smart Images

Figure CN119695364A_ABST
Abstract
Description
[0001] This application is a divisional application of application number 2020800108842, application date January 30, 2020, and invention name “Packaging material for all-solid-state batteries and all-solid-state batteries using the same”. Technical Field
[0002] The present invention relates to a packaging material for an all-solid-state battery and an all-solid-state battery using the packaging material. More specifically, it relates to a packaging material for an all-solid-state battery containing a sulfide-based solid electrolyte and an all-solid-state battery using the packaging material. Background Art
[0003] Secondary batteries such as lithium-ion batteries are widely used in portable electronic devices, electric vehicles powered by electricity, and hybrid electric vehicles. As a battery that improves the safety of lithium-ion batteries, all-solid lithium batteries that use inorganic solid electrolytes instead of organic solvent electrolytes are being studied. All-solid lithium batteries are safer than lithium batteries in that they are less likely to experience thermal runaway caused by short circuits, etc.
[0004] Among inorganic solid electrolytes, sulfide-based solid electrolytes have high ion conductivity compared to oxide-based solid electrolytes, and have more advantages in obtaining higher-performance all-solid batteries. However, since all-solid batteries using sulfide-based solid electrolytes contain sulfur, sometimes the water that penetrates into the battery reacts with the sulfur to generate toxic hydrogen sulfide. Therefore, if the packaging material of the battery is damaged, the hydrogen sulfide may leak. In order to prevent hydrogen sulfide leakage, for example, patent documents 1 and 2 propose all-solid batteries with a safe design that captures the generated hydrogen sulfide to achieve detoxification.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-103283
[0008] Patent Document 2: Japanese Patent Application Publication No. 2008-103288 Summary of the invention
[0009] Problems to be Solved by the Invention
[0010] However, the methods described in Patent Documents 1 and 2 have the problem that the production of the battery requires a great deal of time and labor, which may become a factor that greatly increases the cost. In addition, hydrogen sulfide is corrosive and may corrode copper foil or aluminum foil as a current collector, thereby causing battery deterioration. However, in the inventions described in Patent Documents 1 and 2, no research has been conducted from the perspective of suppressing corrosion caused by hydrogen sulfide.
[0011] An object of the present invention is to provide a packaging material for an all-solid-state battery containing a sulfide-based solid electrolyte, which can render hydrogen sulfide harmless when it is generated and can suppress corrosion of a current collector, and an all-solid-state battery using the packaging material.
[0012] Means for solving problems
[0013] As materials that can render hydrogen sulfide harmless, alkali metals or alkaline earth metals are known. As methods of using these materials, methods such as coating a layer containing these materials can be cited. However, in the case of coating a layer containing the above-mentioned material on a packaging material, it is difficult to seal it using heat sealing like a conventional laminated film. Therefore, it is necessary to form a layer containing the above-mentioned material in advance in a manner that covers the electrode components, or to form it around the packaging material. In the case of forming a layer containing the above-mentioned material around the packaging material, it is necessary to provide a layer containing the above-mentioned material after stamping. This is to prevent the problem of the layer containing the above-mentioned material being easily broken or peeled off during stamping. When these methods are adopted, the manufacture of the battery requires a lot of time and labor.
[0014] On the other hand, a method of dispersing alkali metals or alkaline earth metals in the sealant layer can also be considered. However, in this case, the resin forming the sealant layer and the alkali metal are poorly mixed, and the sealant layer composed of the mixed materials becomes very brittle, resulting in disadvantages such as reduced sealing strength.
[0015] In view of the above circumstances, the present inventors have conducted repeated and intensive studies and have completed the following invention: by using ionic polymer materials such as olefin-metal ion compounds called ionomers, hydrogen sulfide can be made non-toxic and a packaging material having the same properties as conventional packaging materials can be produced.
[0016] That is, the present invention provides a packaging material for an all-solid-state battery, which is a packaging material for an all-solid-state battery containing a sulfide-based solid electrolyte, and comprises at least a substrate layer, a barrier layer, and a sealant layer in sequence, wherein the sealant layer contains an ionomer.
[0017] According to the above-mentioned all-solid battery packaging material, in the all-solid battery using the packaging material, when hydrogen sulfide is generated inside the packaging material, the ionomer configured in the sealant layer closer to the inner side of the packaging material than the barrier layer can make the hydrogen sulfide harmless, thereby suppressing the corrosion of the collector inside the packaging material. The reason why the ionomer can make hydrogen sulfide harmless is that the metal ions forming the ionomer react with hydrogen sulfide, so that hydrogen sulfide is converted into metal sulfide. Thus, the degradation of the all-solid battery can be suppressed. In addition, since the ionomer makes hydrogen sulfide harmless, even if the packaging material of the all-solid battery is destroyed, the leakage of hydrogen sulfide can be suppressed. Therefore, by using the above-mentioned all-solid battery packaging material, a safer all-solid battery can be provided. In addition, the above-mentioned packaging material does not need to go through a special process, and can be manufactured by the same method as the traditional method, and the packaging material itself has the function of making hydrogen sulfide harmless, so when manufacturing the all-solid battery, it is also possible to manufacture the all-solid battery by the same method as the traditional method without going through a special process.
[0018] In the all-solid-state battery packaging material, the ionomer may contain an ethylene-based ionomer resin.
[0019] In the all-solid battery packaging material, the metal ions forming the ionomer may contain zinc ions. Zinc ions have high reactivity with hydrogen sulfide and can effectively convert hydrogen sulfide into zinc sulfide. Therefore, hydrogen sulfide can be rendered harmless more quickly and more effectively, thereby further suppressing the corrosion of the collector.
[0020] In the packaging material for all-solid batteries, the sealant layer may include a mixed resin layer, which contains a polypropylene resin and an ethylene ionomer resin as the ionomer that is incompatible with the polypropylene resin. In addition, the mixed resin layer may further contain a compatibilizer, which has a portion compatible with the polypropylene resin and a portion compatible with the ethylene ionomer resin. The mixed resin layer becomes a layer that has both heat sealability and the function of rendering hydrogen sulfide harmless at a high level. It should be noted that since the ethylene ionomer is incompatible with the polypropylene resin, the mixed resin layer usually has a sea island structure in which the ethylene ionomer is dispersed in the polypropylene resin. By adding the compatibilizer, the adhesion of the sea island interface can be improved, thereby further improving the sealing strength after heat sealing.
[0021] The content of the ionomer in the mixed resin layer may be 1 to 40% by mass based on the total solid content of the mixed resin layer. In this case, the packaging material can have both heat-sealing properties and the function of rendering hydrogen sulfide harmless at a higher level.
[0022] In the all-solid battery packaging material, the sealant layer is composed of multiple layers, at least one of which may be a layer containing the ionomer, and at least one other layer may be a layer containing a polypropylene resin. When the sealant layer has the above structure, the layer containing the ionomer can exhibit a function of rendering hydrogen sulfide harmless, and the layer containing the polypropylene resin can exhibit excellent heat sealing properties.
[0023] In the all-solid battery packaging material, an anti-corrosion treatment layer may be provided on one or both surfaces of the barrier layer. The anti-corrosion treatment layer can prevent corrosion of the barrier layer, and the anti-corrosion treatment layer can improve the adhesion between the barrier layer and its adjacent layers.
[0024] In the all-solid battery packaging material, the anti-corrosion treatment layer may contain: cerium oxide, 1 to 100 parts by mass of phosphoric acid or phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer. According to such a packaging material, the resistance to hydrogen sulfide is excellent, so that the barrier layer of the packaging material can be inhibited from being corroded by hydrogen sulfide. In addition, by having the above-mentioned anti-corrosion treatment layer, it is easy to maintain the adhesion between the sealant layer and the barrier layer.
[0025] In addition, the present invention provides an all-solid-state battery comprising: a battery element containing a sulfide-based solid electrolyte, a current output terminal extending from the battery element, and a packaging material for the all-solid-state battery of the present invention that clamps the current output terminal and accommodates the battery element.
[0026] Effects of the Invention
[0027] According to the present invention, it is possible to provide a packaging material for an all-solid-state battery containing a sulfide-based solid electrolyte, which can render hydrogen sulfide harmless when generated and can suppress corrosion of a current collector, and an all-solid-state battery using the packaging material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [ Figure 1 ] is a schematic cross-sectional view of a packaging material for an all-solid-state battery according to one embodiment of the present invention.
[0029] [ Figure 2 ] is a schematic cross-sectional view of a packaging material for an all-solid-state battery according to one embodiment of the present invention.
[0030] [ Figure 3 ] is a schematic cross-sectional view of a packaging material for an all-solid-state battery according to one embodiment of the present invention.
[0031] [ Figure 4 ] is a perspective view of an all-solid-state battery involved in one embodiment of the present invention.
[0032] [ Figure 5 ] is a schematic diagram illustrating a method for preparing an evaluation sample in an embodiment.
[0033] [ Figure 6 ] is a schematic diagram illustrating a method for preparing an evaluation sample in an embodiment. DETAILED DESCRIPTION
[0034] Hereinafter, the preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that in the accompanying drawings, the same or equivalent parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0035] [Encapsulation materials for all-solid-state batteries]
[0036] Figure 1 : is a cross-sectional view schematically showing an embodiment of the all-solid-state battery packaging material of this embodiment. Figure 1 As shown in FIG. 1 , the packaging material (packaging material for all-solid-state battery) 10 of the present embodiment is a laminated body, which is laminated in this order: a base material layer 11, an adhesive layer 12 (sometimes referred to as a first adhesive layer 12) formed on one surface of the base material layer 11, a barrier layer 13 formed on the surface of the first adhesive layer 12 opposite to the base material layer 11, an anti-corrosion treatment layer 14 formed on the surface of the barrier layer 13 opposite to the first adhesive layer 12, an adhesive layer 17 (sometimes referred to as a second adhesive layer 17) formed on the surface of the anti-corrosion treatment layer 14 opposite to the barrier layer 13, and a sealant layer 16 formed on the surface of the second adhesive layer 17 opposite to the anti-corrosion treatment layer 14. In the packaging material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the packaging material 10 is used in a manner such that the base material layer 11 faces the outside of the all-solid-state battery and the sealant layer 16 faces the inside of the all-solid-state battery. Each layer is described below.
[0037] <Base material layer 11>
[0038] The substrate layer 11 is provided for imparting heat resistance to the sealing process during the manufacture of the all-solid-state battery, and for pinholes that may be caused during processing or circulation, and preferably uses an insulating resin layer. As such a resin layer, for example, a stretched or unstretched film such as a polyester film, a polyamide film, or a polypropylene film can be used as a single layer or a multilayer film stacked with more than two layers. A coextruded multilayer stretched film formed by coextruding a polyethylene terephthalate film (PET) and a nylon film (Ny) with an adhesive resin and then applying a stretching treatment can also be used.
[0039] The base layer 11 may be provided by directly coating on the barrier layer 13 described later. In this case, the first adhesive layer 12 described later is not necessary. As a method of forming the base layer by coating, a method of coating a resin coating liquid such as a urethane resin, an acrylic resin, or a polyester resin, and curing it by ultraviolet irradiation, high temperature heating, aging (curing) treatment, etc. may be adopted. The coating method is not particularly limited, and various methods such as a gravure coating method, a reverse coating method, a roll coating method, and a rod coating method may be adopted.
[0040] The thickness of the substrate layer 11 is preferably 3 to 40 μm, more preferably 5 to 25 μm. By making the thickness of the substrate layer 11 3 μm or more, the pinhole resistance and insulation of the all-solid battery packaging material 10 tend to be improved. On the other hand, by making the thickness of the substrate layer 11 40 μm or less, the deep drawing formability of the all-solid battery packaging material 10 tends to be further improved.
[0041] <First Adhesive Layer 12>
[0042] The first adhesive layer 12 is a layer for bonding the substrate layer 11 and the barrier layer 13. Specific examples of the material constituting the first adhesive layer 12 include polyurethane resins obtained by reacting a bifunctional or higher-functional isocyanate with a main agent such as polyester polyol, polyether polyol, acrylic polyol, carbonate polyol, and the like.
[0043] The above-mentioned various polyols can be used alone or in combination of two or more, depending on the functions and properties required of the packaging material.
[0044] In addition, various other additives and stabilizers may be mixed into the polyurethane resin according to the performance required of the adhesive.
[0045] The thickness of the first adhesive layer 12 is not particularly limited, but is preferably 1 to 10 μm, more preferably 3 to 7 μm, for example, from the viewpoint of obtaining desired adhesive strength, followability, and processability.
[0046] <Barrier layer 13>
[0047] The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the interior of the all-solid-state battery. In addition, the barrier layer 13 has ductility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, or metal vapor-deposited films, inorganic oxide vapor-deposited films, carbon-containing inorganic oxide vapor-deposited films, and films provided with these vapor-deposited films can be used. As a film provided with a vapor-deposited film, for example, an aluminum vapor-deposited film and an inorganic oxide vapor-deposited film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, from the aspects of mass (specific gravity), moisture resistance, processability and cost, metal foil is preferred, and aluminum foil is more preferred.
[0048] As aluminum foil, from the aspect of being able to impart the desired ductility during molding, it is particularly preferred to use a soft aluminum foil that has been annealed, but in order to further impart pinhole resistance and ductility during molding, it is more preferred to use an aluminum foil containing iron. In 100% by mass of aluminum foil, the iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass. By making the iron content 0.1% or more by mass, a packaging material 10 having better pinhole resistance and ductility can be obtained. By making the iron content 9.0% or less by mass, a packaging material 10 having better flexibility can be obtained.
[0049] The thickness of the barrier layer 13 is not particularly limited, but is preferably 9 to 200 μm, more preferably 15 to 100 μm, in consideration of barrier properties, pinhole resistance, and processability.
[0050] When aluminum foil is used as the barrier layer 13, untreated aluminum foil may be used, but degreased aluminum foil is preferably used.
[0051] In addition, when performing the degreasing process on the aluminum foil, the degreasing process may be performed on only one side of the aluminum foil, or may be performed on both sides.
[0052] <Anti-corrosion treatment layer 14>
[0053] The anticorrosion treatment layer 14 is provided to prevent corrosion of the metal foil (metal foil layer) etc. constituting the barrier layer 13. The anticorrosion treatment layer 14 can be formed by, for example, degreasing treatment, hydrothermal reforming treatment, anodizing treatment, chemical conversion treatment or a combination of these treatments.
[0054] As degreasing treatment, acid degreasing or alkali degreasing can be cited. As acid degreasing, methods using inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and fluoric acid alone, or using a mixture thereof, etc. can be cited. In addition, as acid degreasing, especially when aluminum foil is used as the barrier layer 13, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the above-mentioned inorganic acid, not only can the degreasing effect of aluminum be obtained, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance. As alkali degreasing, methods using sodium hydroxide, etc. can be cited.
[0055] Examples of the hydrothermal modification treatment include a boehmite treatment in which the aluminum foil is immersed in boiling water to which triethanolamine has been added.
[0056] Examples of the anodizing treatment include an alumite treatment.
[0057] As chemical conversion treatment, there are immersion type and coating type. As immersion type chemical conversion treatment, for example, there are chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of mixed phases thereof. On the other hand, as coating type chemical conversion treatment, there is a method of coating a coating agent having anticorrosive performance on the barrier layer 13.
[0058] Among these anti-corrosion treatments, when at least a portion of the anti-corrosion treatment layer is formed by any one of hydrothermal modification, anodic oxidation, and chemical conversion treatment, it is preferred to perform the above-mentioned degreasing treatment in advance. It should be noted that when a metal foil that has been subjected to a degreasing treatment such as a metal foil that has undergone an annealing process is used as the barrier layer 13, it is not necessary to perform the degreasing treatment again when forming the anti-corrosion treatment layer 14.
[0059] The coating agent used for the coating type chemical conversion treatment preferably contains trivalent chromium. In addition, the coating agent may contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers described below.
[0060] In addition, in the above-mentioned treatments, especially in the hydrothermal modification treatment and the anodizing treatment, the surface of the aluminum foil is dissolved by a treatment agent, thereby forming an aluminum compound (boehmite, anodized aluminum) with excellent corrosion resistance. Therefore, a co-continuous structure is formed from the barrier layer 13 using the aluminum foil to the anti-corrosion treatment layer 14, so that the above-mentioned treatment is included in the definition of the chemical conversion treatment. On the other hand, as described later, the anti-corrosion treatment layer 14 can also be formed using only a simple coating method that is not included in the definition of the chemical conversion treatment. As this method, for example, a method of using a sol of a rare earth element oxide such as cerium oxide with an average particle size of less than 100 nm as a material having an anti-corrosion effect on aluminum (corrosion inhibitor effect) and also suitable for environmental aspects can be cited. By using this method, even a general coating method can be used to impart an anti-corrosion effect to metal foils such as aluminum foil.
[0061] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, and ether-based solvents. Among them, water-based sols are preferred.
[0062] In the above rare earth element oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, and lactic acid are usually used as dispersion stabilizers to stabilize the dispersion. Among these dispersion stabilizers, phosphoric acid is particularly promising because, in the packaging material 10, (1) the dispersion of the sol is stabilized; (2) the aluminum chelating ability of phosphoric acid is utilized to improve the adhesion with the barrier layer 13; and (3) even at low temperatures, phosphoric acid is easily dehydrated and condensed, thereby improving the cohesion of the anti-corrosion treatment layer 14 (oxide layer).
[0063] As the above-mentioned phosphoric acid or its salt, orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid or their alkali metal salts or ammonium salts can be listed. Among these, the functional performance in the packaging material 10 is preferably condensed phosphoric acid such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, supermetaphosphoric acid, or their alkali metal salts or ammonium salts. In addition, considering the dry film-forming property (drying ability, energy) when the anti-corrosion treatment layer 14 composed of rare earth element oxides is formed by using the sol of the above-mentioned rare earth element oxides using various coating methods, and from the perspective of excellent dehydration condensation at low temperatures, sodium salts are preferred. As phosphates, water-soluble salts are preferred.
[0064] The mixing ratio of phosphoric acid (or its salt) to rare earth element oxide is preferably 1 to 100 parts by mass relative to 100 parts by mass of rare earth element oxide. If the mixing ratio is 1 part by mass or more relative to 100 parts by mass of rare earth element oxide, the rare earth element oxide sol becomes more stable, and the function of the packaging material 10 becomes better. The mixing ratio is more preferably 5 parts by mass or more relative to 100 parts by mass of rare earth element oxide. In addition, if the mixing ratio is less than 100 parts by mass relative to 100 parts by mass of rare earth element oxide, the function of the rare earth element oxide sol is improved. The mixing ratio is more preferably less than 50 parts by mass, and further preferably less than 20 parts by mass relative to 100 parts by mass of rare earth element oxide.
[0065] The anti-corrosion treatment layer 14 formed by the rare earth element oxide sol is an aggregate of inorganic particles, so even after the drying and curing process, the cohesion of the layer itself may be reduced. Therefore, in this case, in order to supplement the cohesion, the anti-corrosion treatment layer 14 is preferably composited with the following anionic polymer or cationic polymer.
[0066] Examples of anionic polymers include polymers having a carboxyl group, such as poly(meth)acrylic acid (or its salt), or copolymers obtained by copolymerizing poly(meth)acrylic acid as a main component. Examples of copolymer components of the copolymer include (meth)acrylic acid alkyl ester monomers (as alkyl groups, there are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.); (meth)acrylamide, N-alkyl (meth)acrylamide, N,N-dialkyl (meth)acrylamide (as alkyl groups, there are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, epoxy, etc.), N-alkoxy (meth)acrylamide, N,N-dialkoxy (meth)acrylamide ( As the alkoxy group, there are methoxy, ethoxy, butoxy, isobutoxy, etc.), amide group-containing monomers such as N-hydroxymethyl (meth) acrylamide, N-phenyl (meth) acrylamide; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate; glycidyl (meth) acrylate, allyl glycidyl ether and other glycidyl group-containing monomers; (meth) acryloxypropyl trimethoxysilane, (meth) acryloxypropyl triethoxysilane and other silane-containing monomers; (meth) acryloxypropyl isocyanate and other isocyanate-containing monomers, etc.
[0067] These anionic polymers play a role in improving the stability of the anti-corrosion treatment layer 14 (oxide layer) obtained using the rare earth element oxide sol. This is achieved by using an acrylic resin component to protect the hard and brittle oxide layer, and by capturing the ion contamination (especially sodium ions) (cation scavenger) from the phosphate contained in the rare earth element oxide sol. That is, in the anti-corrosion treatment layer 14 obtained using the rare earth element oxide sol, when it contains alkali metal ions such as sodium or alkaline earth metal ions, the anti-corrosion treatment layer 14 is prone to deterioration starting from the area containing the ions. Therefore, the sodium ions and the like contained in the rare earth element oxide sol are fixed by using anionic polymers, thereby improving the resistance of the anti-corrosion treatment layer 14.
[0068] The anti-corrosion treatment layer 14 formed by combining anionic polymer and rare earth element oxide sol has the same corrosion resistance as the anti-corrosion treatment layer 14 formed by chromating aluminum foil. The anionic polymer is preferably a structure formed by cross-linking a polyanionic polymer that is essentially water-soluble. As a cross-linking agent for forming this structure, for example, compounds having an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group can be cited.
[0069] Examples of the compound having an isocyanate group include diisocyanates such as toluene diisocyanate, meta-xylylene diisocyanate or its hydride, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or its hydride, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyols such as trimethylolpropane, biuret bodies obtained by reacting these isocyanates with water, or isocyanate urea bodies as trimers; or blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, etc.
[0070] Examples of the compound having a glycidyl group include: epoxy compounds formed by reacting epichlorohydrin with diols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol; epoxy compounds formed by reacting epichlorohydrin with polyols such as glycerol, polyglycerol, trimethylolpropane, pentaerythritol, and sorbitol; epoxy compounds formed by reacting epichlorohydrin with dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid; and the like.
[0071] Examples of the compound having a carboxyl group include various aliphatic or aromatic dicarboxylic acids, etc. In addition, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid may also be used.
[0072] Examples of compounds having an oxazoline group include compounds copolymerized with acrylic monomers such as (meth)acrylic acid, alkyl (meth)acrylates, and hydroxyalkyl (meth)acrylates, for example, when using a low molecular weight compound having two or more oxazoline units or a polymerizable monomer such as isopropenyl oxazoline.
[0073] In addition, anionic polymers can be reacted with silane coupling agents, and more specifically, the carboxyl groups of anionic polymers can be reacted selectively with the functional groups of silane coupling agents, so that the crosslinking points become siloxane bonds. In this case, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, etc. can be used. Among these, considering the reactivity with anionic polymers or their copolymers, epoxysilane, aminosilane, and isocyanatesilane are particularly preferred.
[0074] The ratio of these crosslinking agents to the anionic polymer is preferably 1 to 50 parts by mass, more preferably 10 to 20 parts by mass, relative to 100 parts by mass of the anionic polymer. If the ratio of the crosslinking agent is 1 part by mass or more relative to 100 parts by mass of the anionic polymer, a crosslinked structure is easily formed sufficiently. If the ratio of the crosslinking agent is 50 parts by mass or less relative to 100 parts by mass of the anionic polymer, the pot life of the coating solution can be increased.
[0075] The method of cross-linking the anionic polymer is not limited to the above-mentioned cross-linking agent, and a method of forming ionic cross-links using titanium or zirconium compounds may be used.
[0076] As cationic polymers, polymers with amines can be listed, and cationic polymers such as polyethyleneimine, ionic polymer complexes composed of polyethyleneimine and polymers with carboxylic acids, primary amine grafted acrylic resins formed by grafting primary amines on acrylic acid main chains, polyallylamine or its derivatives, aminophenols, etc. can be listed. As polyallylamine, for example, homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, dimethylallylamine, etc. can be listed. These amines can be free amines or compounds stabilized by acetic acid or hydrochloric acid. In addition, maleic acid, sulfur dioxide, etc. can also be used as copolymer components. In addition, types that are given thermal crosslinking properties by partially methoxylating primary amines can also be used, and aminophenol can also be used. Allylamine or its derivatives are particularly preferred.
[0077] The cationic polymer is preferably used in combination with a crosslinking agent having a functional group such as a carboxyl group or a glycidyl group that can react with an amine / imine. As a crosslinking agent that can be used in combination with a cationic polymer, a polymer having a carboxylic acid that forms an ionic polymer complex with polyethyleneimine can also be used, for example, polycarboxylic acids (salts) such as polyacrylic acid or its ionic salts, or copolymers formed by introducing comonomers therein, polysaccharides having a carboxyl group such as carboxymethyl cellulose or its ionic salts, etc. can be cited.
[0078] From the perspective of improving adhesion, cationic polymers are more preferred materials. In addition, like the above-mentioned anionic polymers, cationic polymers are also water-soluble and can form a cross-linked structure to impart water resistance, so they are more preferred. The cross-linking agent for forming a cross-linked structure in the cationic polymer can use the cross-linking agent described in the anionic polymer. In the case of using a rare earth element oxide sol as the anti-corrosion treatment layer 14, a cationic polymer can also be used instead of the above-mentioned anionic polymer as its protective layer.
[0079] In the anti-corrosion treatment layer obtained by chemical conversion treatment represented by chromate treatment, in order to form an inclined structure with the aluminum foil, a chemical conversion treatment agent formed by mixing fluoric acid, hydrochloric acid, nitric acid, sulfuric acid or their salts is particularly used to treat the aluminum foil, and then chromium or non-chromium compounds are allowed to act, thereby forming a chemical conversion treatment layer on the aluminum foil. However, regarding the above-mentioned chemical conversion treatment, since an acid is used in the chemical conversion treatment agent, it is accompanied by deterioration of the working environment and corrosion of the coating device. On the other hand, the above-mentioned coating type anti-corrosion treatment layer 14 is different from the chemical conversion treatment represented by chromate treatment, and does not need to form an inclined structure for the barrier layer 13 using aluminum foil. Therefore, the properties of the coating agent are not limited by acidity, alkalinity, neutrality, etc., and a good working environment can be achieved. In addition, from the perspective of environmental hygiene, the coating type anti-corrosion treatment layer 14 is also preferred in terms of the requirement for an alternative to the chromate treatment using a chromium compound.
[0080] Based on the above, examples of combinations of the above-mentioned coating-type anti-corrosion treatments include: (1) only rare earth element oxide sol; (2) only anionic polymer; (3) only cationic polymer; (4) rare earth element oxide sol + anionic polymer (laminated composite); (5) rare earth element oxide sol + cationic polymer (laminated composite); (6) (rare earth element oxide sol + anionic polymer: laminated composite) / cationic polymer (multilayer); (7) (rare earth element oxide sol + cationic polymer: laminated composite) / anionic polymer (multilayer), etc. Among these, (1) and (4) to (7) are preferred, and (4) to (7) are particularly preferred. However, this embodiment is not limited to the above-mentioned combinations. For example, as a selective example of anti-corrosion treatment, cationic polymers are very preferred materials in terms of good adhesion with the modified polyolefin resin listed in the description of the second adhesive layer or sealant layer described later. Therefore, the design can be as follows: when the second adhesive layer or sealant layer is composed of a modified polyolefin resin, a cationic polymer is provided on the surface in contact with the second adhesive layer or sealant layer (for example, compositions (5) and (6) etc.).
[0081] In addition, the anti-corrosion treatment layer 14 is not limited to the above-mentioned layer. For example, it can also be formed by using a treatment agent in which phosphoric acid and a chromium compound are mixed in a resin binder (aminophenol, etc.) as a coating type chromate as a known technology. If this treatment agent is used, it can become a layer having both anti-corrosion function and tight adhesion. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent formed by liquefying a rare earth element oxide sol and a polycationic polymer or a polyanionic polymer in advance can be used to form a layer having both anti-corrosion function and tight adhesion.
[0082] Regardless of whether it is a multi-layer structure or a single-layer structure, the mass per unit area of the anticorrosion treatment layer 14 is preferably 0.005 to 0.200 g / m 2 , more preferably 0.010 to 0.100 g / m 2 If the mass per unit area is 0.005 g / m 2 If the mass per unit area exceeds 0.200 g / m 2 , the anti-corrosion function will not change much. On the other hand, when using rare earth element oxide sol, when the coating is thick, the curing caused by the heat during drying is insufficient, which may be accompanied by a decrease in cohesion. It should be noted that the thickness of the anti-corrosion treatment layer 14 can be converted from its specific gravity.
[0083] From the viewpoint of easily maintaining the close adhesion between the sealant layer 16 and the barrier layer 13, the anti-corrosion treatment layer 14 may be, for example, a method containing cerium oxide, 1 to 100 parts by mass of phosphoric acid or phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer; or a method formed by subjecting the barrier layer 13 to a chemical conversion treatment; or a method formed by subjecting the barrier layer 13 to a chemical conversion treatment and containing a cationic polymer.
[0084] <Second Adhesive Layer 17>
[0085] The second adhesive layer 17 is a layer for bonding the barrier layer 13 formed with the anticorrosion treatment layer 14 and the sealant layer 16. For the second adhesive layer 17, a conventional adhesive for bonding a barrier layer and a sealant layer can be used.
[0086] When the anti-corrosion treatment layer 14 has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 17 is preferably a layer containing a compound reactive with the above-mentioned polymer contained in the anti-corrosion treatment layer 14 (hereinafter also referred to as a "reactive compound").
[0087] For example, when the anticorrosion treatment layer 14 contains a cationic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer. When the anticorrosion treatment layer 14 contains an anionic polymer, the second adhesive layer 17 contains a compound reactive with the anionic polymer. In addition, when the anticorrosion treatment layer 14 contains a cationic polymer and an anionic polymer, the second adhesive layer 17 contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 17 does not necessarily have to contain the above two compounds, and may also contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means forming a covalent bond with a cationic polymer or an anionic polymer. In addition, the second adhesive layer 17 may further contain an acid-modified polyolefin resin.
[0088] Examples of the compound reactive with the cationic polymer include at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxyl group, and a compound having an oxazoline group.
[0089] As these polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, and compounds having oxazoline groups, polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, and compounds having oxazoline groups previously exemplified as crosslinking agents for making cationic polymers into crosslinked structures can be cited. Among these, polyfunctional isocyanate compounds are preferred because of their high reactivity with cationic polymers and the ease with which crosslinked structures can be formed.
[0090] As the reactive compound with anionic polymer, at least one compound selected from the group consisting of glycidyl compounds, compounds with oxazoline groups can be enumerated. As these glycidyl compounds, compounds with oxazoline groups, glycidyl compounds previously exemplified as the cross-linking agent for making cationic polymer become cross-linked structure, compounds with oxazoline groups etc. can be enumerated. Among these, from the aspect high with the reactivity of anionic polymer, preferred glycidyl compounds.
[0091] When the second adhesive layer 17 contains an acid-modified polyolefin resin, the reactive compound preferably also has reactivity with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). Thus, the adhesion to the anti-corrosion treatment layer 14 is further improved. In addition, the acid-modified polyolefin resin becomes a cross-linked structure, and the solvent resistance of the packaging material 10 is further improved.
[0092] The content of the reactive compound is preferably an equal amount to 10 times the amount of the acidic group in the acid-modified polyolefin resin. If it is equal or more, the reactive compound fully reacts with the acidic group in the acid-modified polyolefin resin. On the other hand, when it exceeds 10 times the amount, the crosslinking reaction with the acid-modified polyolefin resin is fully saturated, so there are unreacted products, and various properties may be reduced. Therefore, the content of the reactive compound is preferably, for example, 5 to 20 parts by mass (solid content ratio) relative to 100 parts by mass of the acid-modified polyolefin resin.
[0093] The acid-modified polyolefin resin is a material obtained by introducing an acidic group into a polyolefin resin. Examples of the acidic group include a carboxyl group, a sulfonic acid group, an anhydride group, and the like, with maleic anhydride group and (meth) acrylic acid group being particularly preferred. As the acid-modified polyolefin resin, for example, the same resin as the modified polyolefin resin (a) used for the first sealant layer 16a described later can be used.
[0094] The second adhesive layer 17 may contain various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0095] From the viewpoint of suppressing the reduction in lamination strength and further suppressing the reduction in insulation, the second adhesive layer 17 contains, for example, an acid-modified polyolefin; and at least one curing agent selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxyl group, a compound having an oxazoline group, and a carbodiimide compound. It should be noted that examples of the carbodiimide compound include N,N'-di-o-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-tolyl-N'-cyclohexylcarbodiimide, N,N'-di-2,2-di-tert-butylphenylcarbodiimide, N-tolyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-dicyclohexylcarbodiimide, and N,N'-di-p-tolylcarbodiimide.
[0096] As the adhesive forming the second adhesive layer 17, for example, a polyurethane-based adhesive obtained by mixing polyester polyol composed of hydrogenated dimer fatty acid and diol and polyisocyanate can be used.
[0097] The thickness of the second adhesive layer 17 is not particularly limited, but is preferably 1 to 10 μm, more preferably 3 to 7 μm, from the viewpoint of obtaining desired adhesive strength and processability.
[0098] <Sealing agent layer 16>
[0099] The sealant layer 16 is a layer that imparts sealability by heat sealing to the packaging material 10. The sealant layer 16 is configured to contain at least an ionomer.
[0100] like Figure 1 As shown, when the sealant layer is a single layer, the sealant layer is an ionomer-containing layer containing an ionomer.
[0101] Ionomers are ionic polymer materials having ionic crosslinks, and have a structure in which molecules of a base copolymer such as ethylene-methacrylic acid copolymer or ethylene-acrylic acid copolymer are crosslinked by metal ions. As the ionomer, known ionomers can be used without particular limitation.
[0102] The metal ions constituting the ionomer are not particularly limited, and examples thereof include zinc ions and sodium ions, but zinc ions are preferred from the viewpoint of rendering hydrogen sulfide more rapidly and effectively harmless. The metal ions may be used alone or in combination of two or more.
[0103] As the basic copolymer constituting the ionomer, there can be cited copolymers consisting of α-olefins such as ethylene and propylene and α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and maleic acid, but from the viewpoint of heat sealability, copolymers consisting of ethylene or propylene and acrylic acid or methacrylic acid are preferred. The basic copolymer can be used alone or in combination of two or more. It should be noted that in this specification, an ionomer using ethylene as a constituent component of the basic copolymer is also referred to as an "ethylene-based ionomer resin".
[0104] The ionomer-containing layer as the sealant layer 16 may be a layer composed only of ionomer (an ionomer single layer in which the ionomer content is 100% by mass), but may also contain components other than the above-mentioned ionomer. The ionomer-containing layer as the sealant layer 16 may also be composed of, for example, a resin composition serving as a base (hereinafter also referred to as a "base resin composition") and an ionomer. It should be noted that, in this specification, a sealant layer containing an ionomer and a resin other than the ionomer (base resin composition) is also referred to as a "mixed resin layer". In addition, the above-mentioned mixed resin layer may further contain a compatibilizer, which has a portion compatible with the resin contained in the base resin composition and a portion compatible with the ionomer. Here, the above-mentioned base resin composition refers to the component after removing the ionomer and the compatibilizer from all the constituent components of the sealant layer 16.
[0105] When the sealant layer 16 is a mixed resin layer containing an ionomer and a base resin composition, the content of the ionomer in the mixed resin layer may be 1% by mass or more and less than 100% by mass, 1 to 70% by mass, 1 to 40% by mass, or 5 to 20% by mass, based on the total solid content of the mixed resin layer. By setting the content of the ionomer within the above range, it is easier to achieve both heat sealing properties and the function of detoxifying hydrogen sulfide at a high level.
[0106] The base resin composition is not particularly limited, and polyolefins such as polyethylene and polypropylene can be cited. For example, the base resin composition includes (A) 60 to 95% by mass of a propylene-ethylene random copolymer and (B) 5 to 40% by mass of a polyolefin elastomer having a melting point of 150° C. or less and containing butene-1 as a comonomer (hereinafter referred to as "resin composition α" depending on the situation).
[0107] [Resin composition α]
[0108] As described above, the resin composition α contains: (A) 60 to 95% by mass of a propylene-ethylene random copolymer and (B) 5 to 40% by mass of a polyolefin elastomer having a melting point of 150° C. or lower and containing butene-1 as a comonomer.
[0109] ((A) Propylene-ethylene random copolymer)
[0110] The (A) propylene-ethylene random copolymer is superior in heat sealability at low temperatures compared to a propylene-ethylene block copolymer and a propylene homopolymer, and can thus improve sealing properties.
[0111] In (A) propylene-ethylene random copolymer, the ethylene content is preferably 0.1 to 10% by mass, more preferably 1 to 7% by mass, and further preferably 2 to 5% by mass. When the ethylene content is 0.1% by mass or more, the effect of reducing the melting point caused by copolymerizing ethylene can be fully obtained, and the sealing characteristics can be further improved while obtaining impact resistance, thereby tending to improve the sealing strength and resistance to molding whitening. When the ethylene content is 10% by mass or less, the melting point can be suppressed from being excessively reduced, thereby tending to more fully suppress the generation of excess sealing parts. It should be noted that the ethylene content can be calculated based on the mixing ratio of the monomers during polymerization.
[0112] The melting point of the (A) propylene-ethylene random copolymer is preferably 120 to 145° C., more preferably 125 to 140° C. When the melting point is 120° C. or higher, the generation of excess sealing portions tends to be more sufficiently suppressed. When the melting point is 145° C. or lower, the sealing properties tend to be further improved.
[0113] (A) The propylene-ethylene random copolymer may be acid-modified, for example, an acid-modified propylene-ethylene random copolymer graft-modified with maleic anhydride. By using the acid-modified propylene-ethylene random copolymer, the adhesion with the tab lead can be maintained even without a tab seal.
[0114] (A) The propylene-ethylene random copolymer may be used alone or in combination of two or more.
[0115] In resin composition α, based on the total solid content of resin composition α, the content of (A) component is 60 to 95% by mass, preferably 60 to 90% by mass, and more preferably 60 to 85% by mass. By making the content of (A) component more than 60% by mass, the sealing characteristics can be improved due to the use of the self-effect of (A) component. In addition, by setting the content of (A) component to more than 60% by mass, the excess existence of (B) component can be prevented, thereby suppressing the reduction of the heat resistance of the sealant layer 16, and suppressing the generation of the excess sealing part. On the other hand, by setting the content of (A) component to less than 95% by mass, the (B) component can be made to contain more than 5% by mass, so that the improvement effect of the heat seal strength caused by the (B) component can be fully obtained.
[0116] ((B) a polyolefin elastomer having a melting point of 150°C or less and containing butene-1 as a comonomer)
[0117] (B) The polyolefin elastomer having a melting point of 150° C. or lower and containing butene-1 as a comonomer contributes to improving the sealing properties and suppressing the occurrence of molding whitening.
[0118] The (B) polyolefin elastomer may be compatible or incompatible with the (A) component, but preferably includes both a compatible (B-1) compatible polyolefin elastomer and an incompatible (B-2) incompatible polyolefin elastomer. Here, when the resin constituting the (A) component is a propylene-ethylene random copolymer, being compatible with the (A) component (compatible) means being dispersed in the propylene-ethylene random copolymer resin constituting the (A) component in a manner such that the dispersed phase size is greater than 1 nm and less than 500 nm. Being incompatible (incompatible) means being dispersed in the propylene-ethylene random copolymer resin constituting the (A) component in a manner such that the dispersed phase size is greater than 500 nm and less than 20 μm.
[0119] Examples of the (B-1) compatible polyolefin elastomer include propylene-butene-1 random copolymers.
[0120] Examples of the (B-2) incompatible polyolefin elastomer include ethylene-butene-1 random copolymers.
[0121] The melting point of the polyolefin elastomer (B) needs to be 150°C or less, but is preferably 60 to 120°C, more preferably 65 to 90°C, from the viewpoint of suppressing the formation of an excessive seal portion, suppressing whitening during molding, and improving the sealing properties. By setting the melting point to 150°C or less, the sealing properties can be improved. In addition, when the melting point is 60°C or more, it is advantageous from the viewpoint of suppressing the formation of an excessive seal portion.
[0122] (B) The polyolefin-based elastomer may be used alone or in combination of two or more.
[0123] In the resin composition α, the content of the component (B) is 5 to 40% by mass, preferably 10 to 40% by mass, and more preferably 15 to 40% by mass, based on the total solid content of the resin composition α. By making the content of the component (B) 5% or more by mass, the improvement effect of the sealing characteristics can be fully obtained. On the other hand, by setting the content of the component (B) to 40% by mass or less, the reduction in the heat resistance of the sealant layer 16 can be suppressed, and the generation of the excess sealing portion can be suppressed.
[0124] When the component (B) includes (B-1) a compatible polyolefin elastomer and (B-2) an incompatible polyolefin elastomer, the content ratio of the two (((B-1) compatible polyolefin elastomer / (B-2) incompatible polyolefin elastomer)) is preferably 0.5 to 3, more preferably 1 to 2 in terms of mass ratio. By setting the content ratio within the above range, the molding whitening resistance and the sealing properties can be improved in a well-balanced manner.
[0125] (Added Ingredients)
[0126] The resin composition α may further contain other components other than the above-mentioned (A) component and (B) component. As other components other than the (A) component and the (B) component, for example, other resins such as LDPE (low-density polyethylene) can be added to improve the winding property and processability. When the total mass of the sealant layer 16 is set to 100 parts by mass, the content of the other resin components added is preferably less than 10 parts by mass. In addition, as components other than the resin, for example, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, a flame retardant, etc. can be listed. When the total mass of the sealant layer 16 is set to 100 parts by mass, the content of other components other than these resins is preferably less than 5 parts by mass.
[0127] In the sealant layer 16, the presence of butene-1 can be confirmed by attribution using FT-IR (Fourier transform infrared spectrometer). In addition, by using a resin composition α mixed with a known amount of elastomer containing a known amount of butene-1, a standard curve is prepared based on the transmittance or absorbance of the characteristic absorption bands of the (A) component and the (B) component, thereby confirming the content of butene-1. In addition, for the butene-1 content of each of the (B-1) compatible polyolefin elastomer and the (B-2) incompatible polyolefin elastomer, the characteristic absorption band of FT-IR can also be used for imaging, and the absorption band from butene-1 in microscopic FT-IR (transmission method) can be mapped for confirmation. It should be noted that in addition to FT-IR, the presence and content of butene-1 can also be confirmed by measuring the sealant layer 16 using NMR.
[0128] 〔Compatibilizer〕
[0129] The sealant layer 16 is a mixed resin layer containing an ionomer and a base resin composition. When the ionomer is incompatible with the resin contained in the base resin composition, the mixed resin layer preferably further contains a compatibilizer, which has a portion compatible with the resin contained in the base resin composition and a portion compatible with the ionomer. For example, when the resin contained in the base resin composition is a polypropylene resin such as (A) a propylene-ethylene random copolymer, and the ionomer is an ethylene ionomer resin that is incompatible with the polypropylene resin, the mixed resin layer preferably contains a compatibilizer, which has a portion compatible with the above-mentioned polypropylene resin and a portion compatible with the above-mentioned ethylene ionomer resin. When the ionomer is incompatible with the resin contained in the base resin composition, the mixed resin layer has an island structure formed by the ionomer being dispersed in the resin contained in the base resin composition. By adding the above-mentioned compatibilizer therein, the adhesion strength of the interface of the island structure can be improved, thereby further improving the sealing strength after heat sealing. The compatibilizer may also improve the adhesion strength of the interface of the sea-island structure formed by the component (A) and the component (B) in the resin composition α.
[0130] As the compatibilizer, graft copolymers and block copolymers can be cited. As the graft copolymer suitable for the compatibilizer, a graft copolymer consisting of a main chain of a polyolefin and a side chain of a polystyrene, a graft copolymer consisting of a main chain of a polyolefin and a side chain of a styrene-acrylonitrile copolymer, etc. can be cited. As the above-mentioned graft copolymer, for example, "Modiper" manufactured by NOF Corporation can be used.
[0131] As block copolymers suitable for compatibilizers, there can be listed: block copolymers having blocks composed of styrene units and blocks composed of ethylene-butylene units; block copolymers having blocks composed of styrene units, blocks composed of ethylene-butylene units, and blocks composed of crystalline olefin units; block copolymers having blocks composed of crystalline ethylene units and blocks composed of ethylene-butylene units; block copolymers having blocks composed of ethylene and blocks composed of ethylene-octene 1; and block copolymers having blocks composed of propylene units and blocks composed of ethylene units. For example, the block composed of propylene units is a portion compatible with a polypropylene resin such as the above-mentioned (A) propylene-ethylene random copolymer, and the block composed of ethylene units is a portion compatible with ionomers such as ethylene ionomer resins. As the above-mentioned block copolymers, for example, "DYNARON" manufactured by JSR, "INTUNE" and "INFUSE" manufactured by DOW can be used.
[0132] In the case where the mixed resin layer contains a compatibilizer, the content of the compatibilizer in the mixed resin layer is preferably 1 to 40% by mass, more preferably 2 to 25% by mass, further preferably 2 to 20% by mass, and particularly preferably 7 to 15% by mass, based on the total solid content of the mixed resin layer. By making the content of the compatibilizer 1% or more, it is easy to increase the adhesion strength of the sea-island interface, thereby easily obtaining the effect of increasing the sealing strength. On the other hand, by making the content of the compatibilizer 40% or less by mass, it is easy to suppress the reduction of the cohesive force and sealing strength of the entire sealant layer 16.
[0133] The thickness of the sealant layer 16 is not particularly limited, but is preferably in the range of 5 to 100 μm, more preferably in the range of 20 to 80 μm. In addition, from the perspective of thin film formation, the thickness of the sealant layer 16 may be 30 μm or less. Even if the all-solid battery packaging material of this embodiment is such a thin film structure, it can suppress the reduction of crack resistance after heat sealing and molding, and at the same time, it can achieve harmlessness to hydrogen sulfide, thereby suppressing corrosion of the collector.
[0134] Preferred embodiments of the all-solid-state battery packaging material of this embodiment have been described in detail above, but the present invention is not limited to these specific embodiments, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.
[0135] For example, in Figure 1, the anti-corrosion treatment layer 14 is shown to be formed on the surface of the barrier layer 13 on the second adhesive layer 17 side, but the anti-corrosion treatment layer 14 may be formed on the surface of the barrier layer 13 on the first adhesive layer 12 side, or may be formed on both surfaces of the barrier layer 13. When the anti-corrosion treatment layer 14 is formed on both surfaces of the barrier layer 13, the structure of the anti-corrosion treatment layer 14 formed on the first adhesive layer 12 side of the barrier layer 13 may be the same as or different from the structure of the anti-corrosion treatment layer 14 formed on the second adhesive layer 17 side of the barrier layer 13. In addition, the anti-corrosion treatment layer 14 may not be provided on any surface of the barrier layer 13.
[0136] exist Figure 1 FIG. 4 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the second adhesive layer 17. Figure 2 The all-solid battery packaging material 20 and Figure 3 As shown in the all-solid battery packaging material 30, the sealant layer 16 may be formed directly on the barrier layer 13 without the second adhesive layer 17. Figure 2 The all-solid battery packaging material 20 and Figure 3 The illustrated all-solid-state battery packaging material 30 may include a second adhesive layer 17 between the barrier layer 13 and the sealant layer 16 .
[0137] exist Figure 1 FIG. 4 shows a case where the sealant layer 16 is formed of a single layer, but Figure 2 The all-solid battery packaging material 20 and Figure 3 As shown in the all-solid battery packaging material 30, the sealant layer 16 can also be formed of more than two layers. The structure of each of the multiple layers forming the sealant layer 16 can be the same or different. It should be noted that when the sealant layer 16 is a multilayer, at least one layer is an ionomer-containing layer containing an ionomer.
[0138] exist Figure 2 In the packaging material 20 for all-solid batteries shown, the sealant layer 16 is composed of a first sealant layer 16a and a second sealant layer 16b. Here, the first sealant layer 16a is the outermost layer of the sealant layer, and the second sealant layer 16b is the innermost layer of the sealant layer. At least one layer selected from the group consisting of the first sealant layer 16a and the second sealant layer 16b is an ionomer-containing layer containing the above-mentioned ionomer. As described above, the ionomer-containing layer can be an ionomer-only layer composed of an ionomer, or a mixed resin layer containing an ionomer, a base resin composition, and a compatibilizer as required.
[0139] The second sealant layer 16b (innermost layer) can be formed using, for example, the same constituent components as the sealant layer 16 in the above-mentioned packaging material 10. When the second sealant layer 16b is an ionomer-containing layer, hydrogen sulfide can be rendered harmless more quickly and efficiently.
[0140] Alternatively, the second sealant layer 16 b may be formed using a material obtained by removing the ionomer and the compatibilizer from the material forming the sealant layer 16 in the above-mentioned packaging material 10 .
[0141] The thickness of the second sealing agent layer 16 b is not particularly limited, but specifically, for example, is preferably in the range of 5 to 100 μm, and may be in the range of 10 to 30 μm from the viewpoint of thinning.
[0142] The first sealant layer 16a (outermost layer, metal foil side layer) can be formed using the same constituent components as the second sealant layer 16b, for example. However, in the first sealant layer 16a, in consideration of aluminum treatment and adhesion, for example, a resin composition containing an adhesive resin composition as a main component and an additive component as required (hereinafter, also referred to as "resin composition β" as the case may be) is preferably used to replace the resin composition α as the base resin composition. That is, the first sealant layer 16a can be formed, for example, by an ionomer, a resin composition β, and a compatibilizer as required, or can be formed only by the resin composition β. When the first sealant layer 16a contains an adhesive resin composition, it is easy to form the sealant layer on the barrier layer without passing through the adhesive layer. In the case where the first sealant layer 16a is formed by an ionomer, a resin composition β, and a compatibilizer as required, it tends to be easy to maintain the adhesion between the sealant layer and the barrier layer.
[0143] [Resin composition β (excluding the above-mentioned ionomer)]
[0144] The adhesive resin composition in the resin composition β is not particularly limited, but preferably contains a modified polyolefin resin (a) component and a macrophase separation thermoplastic elastomer (b) component. In addition, the additive component preferably contains atactic polypropylene or atactic propylene-α-olefin copolymer (c). The following describes each component.
[0145] (Modified polyolefin resin (a))
[0146] The modified polyolefin resin (a) is preferably a resin obtained by graft-modifying a polyolefin resin with an unsaturated carboxylic acid derivative component derived from any of an unsaturated carboxylic acid, an anhydride of an unsaturated carboxylic acid, and an ester of an unsaturated carboxylic acid.
[0147] Examples of the polyolefin resin include low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-α-olefin copolymers, homo-, block- or random-polypropylene, propylene-α-olefin copolymers and the like.
[0148] Examples of the compound used when graft-modifying these polyolefin resins include unsaturated carboxylic acid derivative components derived from any of unsaturated carboxylic acids, anhydrides of unsaturated carboxylic acids, and esters of unsaturated carboxylic acids.
[0149] Specific examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid.
[0150] Examples of the anhydride of unsaturated carboxylic acid include anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride.
[0151] Examples of the ester of unsaturated carboxylic acid include esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconic acid, dimethyl tetrahydrophthalic anhydride, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate.
[0152] The modified polyolefin resin (a) can be manufactured by graft polymerization (graft modification) of 0.2 to 100 parts by mass of the above-mentioned unsaturated carboxylic acid derivative component relative to 100 parts by mass of the polyolefin resin as a base in the presence of a free radical initiator. The reaction temperature of the graft modification is preferably 50 to 250° C., more preferably 60 to 200° C. In addition, the reaction time can be appropriately set according to the manufacturing method, for example, in the case of melt graft polymerization using a twin-screw extruder, it is within the residence time of the extruder, specifically, preferably 2 to 30 minutes, more preferably 5 to 10 minutes. It should be noted that the graft modification can be implemented under any conditions of normal pressure or pressurization.
[0153] Examples of the radical initiator used for graft modification include organic peroxides such as alkyl peroxides, aryl peroxides, acyl peroxides, ketone peroxides, peroxyketals, peroxycarbonates, peroxyesters, and hydroperoxides.
[0154] These organic peroxides can be appropriately selected and used according to the conditions of the above-mentioned reaction temperature and reaction time. For example, in the case of melt graft polymerization using a twin-screw extruder, alkyl peroxides, peroxyketals, and peroxyesters are preferred, and specifically, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)-hexyne-3, diisopropylbenzene peroxide, etc. are preferred.
[0155] As the modified polyolefin resin (a), a polyolefin resin modified with maleic anhydride is preferred, and for example, "Admer" manufactured by Mitsui Chemicals, Inc., "Modic" manufactured by Mitsubishi Chemical Corporation, etc. are suitable. Such a modified polyolefin resin (a) component has excellent reactivity with various metals or polymers having various functional groups, and thus this reactivity can be utilized to impart adhesion to the first sealant layer 16a.
[0156] (Macrophase-separated thermoplastic elastomer (b))
[0157] The macrophase-separated thermoplastic elastomer (b) forms a macrophase-separated structure with respect to the modified polyolefin resin (a) so that the dispersed phase size is within a range of more than 200 nm and 50 μm or less.
[0158] By making the adhesive resin composition contain the macrophase separation thermoplastic elastomer (b) component, the residual stress generated when the modified polyolefin resin (a) component, which is the main component constituting the first sealant layer 16a, is laminated can be released, and the first sealant layer 16a can be given viscoelastic adhesiveness. Therefore, the packaging material 20 with further improved adhesion of the first sealant layer 16a can be obtained.
[0159] The macrophase-separated thermoplastic elastomer (b) exists in the form of islands on the modified polyolefin resin (a), but when the dispersed phase size is 200 nm or less, it is difficult to provide improvement in viscoelastic adhesion. On the other hand, when the dispersed phase size exceeds 50 μm, since the modified polyolefin resin (a) and the macrophase-separated thermoplastic elastomer (b) are essentially incompatible, the lamination adaptability (processability) is significantly reduced, and the physical strength of the first sealant layer 16a is easily reduced. Based on the above, the dispersed phase size is preferably 500 nm to 10 μm.
[0160] Examples of such macrophase-separated thermoplastic elastomers (b) include polyolefin-based thermoplastic elastomers obtained by copolymerizing ethylene and / or propylene with an α-olefin selected from 1-butene, 1-pentene, 1-hexene, 1-octene and 4-methyl-1-pentene.
[0161] As the macrophase-separated thermoplastic elastomer (b) component, commercially available products can be used, for example, "Tafmer" manufactured by Mitsui Chemicals, "Zelas" manufactured by Mitsubishi Chemical Corporation, "Catalloy" manufactured by Montell Corporation, etc. are suitable.
[0162] In the above-mentioned resin composition β, the content of the macro-phase separation thermoplastic elastomer (b) component relative to the modified polyolefin resin (a) component is preferably 1 to 40 parts by mass, and more preferably 5 to 30 parts by mass, relative to 100 parts by mass of the modified polyolefin resin (a) component. Here, when the content of the macro-phase separation thermoplastic elastomer (b) component is less than 1 part by mass, it is not possible to expect an improvement in the adhesion of the first sealant layer. On the other hand, when the content of the macro-phase separation thermoplastic elastomer (b) component exceeds 40 parts by mass, since the compatibility between the modified polyolefin resin (a) component and the macro-phase separation thermoplastic elastomer (b) component is low, the processability is easily significantly reduced. In addition, since the macro-phase separation thermoplastic elastomer (b) component is not a resin that exhibits adhesion, the adhesion of the first sealant layer 16a relative to other layers such as the second sealant layer 16b or the anti-corrosion treatment layer 14 is easily reduced.
[0163] (Atactic polypropylene or atactic propylene-α-olefin copolymer (c))
[0164] The resin composition β preferably contains atactic polypropylene or atactic propylene-α-olefin copolymer (hereinafter referred to as component (c)) as an additive component. Here, component (c) is a completely non-crystalline resin component.
[0165] Next, the effect of adding the additive component (c) to the adhesive resin composition as a main component in the above-mentioned resin composition β will be described.
[0166] Component (c) is compatible with the modified polyolefin resin (a) component in the adhesive resin composition in a molten state, but when crystallization occurs with cooling, component (c) is discharged outside the crystal and evenly dispersed around the spherulites. Therefore, component (c) does not hinder the crystallinity of the modified polyolefin resin (a) component in the adhesive resin composition as the main component. In addition, by adding component (c) to the above-mentioned resin composition β, the concentration of the modified polyolefin resin (a) component is diluted by component (c) and crystal growth is inhibited, so the crystal size (spherulite size) of the adhesive component of the base resin (i.e., the modified polyolefin resin (a) component) may become smaller. In addition, component (c) discharged outside the crystal is evenly dispersed around the tiny spherulites of the modified polyolefin resin (a) component.
[0167] However, it has been known that a "whitening phenomenon" occurs when a packaging material is cold-formed. Here, the principle of the whitening phenomenon is explained.
[0168] (1) The modified polyolefin resin (a) in the resin composition β is crystallized by heat treatment during heat lamination.
[0169] (2) Since the modified polyolefin resin (a) and the macrophase-separated thermoplastic elastomer (b) are incompatible, a strain is generated at the interface between the two due to the crystallization behavior of (1).
[0170] (3) Since stress is applied during molding, cracks are generated at the interface between the two, forming pores and cracks.
[0171] (4) Due to the gaps and cracks, light is scattered, and the whitening phenomenon is caused by the optical random reflection of light.
[0172] That is, it can be seen that in order to suppress the whitening phenomenon, it is important to "prevent the modified polyolefin resin (a) from crystallizing due to the heat during heat lamination (i.e., make it difficult to crystallize)" and "improve the adhesion between the modified polyolefin resin (a) and the macro-phase separation thermoplastic elastomer (b)".
[0173] In contrast, by adding component (c) as an additive component to the adhesive resin composition that can become the main component of the first sealant layer 16a, the crystal size (spherulite size) of the modified polyolefin resin (a) component can be reduced, thereby obtaining a soft and viscous film property. In addition, it is believed that by uniformly dispersing component (c) around the modified polyolefin resin (a), stress can be uniformly relieved, thereby suppressing the generation of void cracks, and thus relieving the "whitening phenomenon" of the packaging material 20 accompanied by stress during molding.
[0174] As described above, by adding component (c) as an additive component to the adhesive resin composition that can be the main component of the first sealant layer 16a, the transparency of the first sealant layer 16a can be improved, and the whitening phenomenon caused by stress during molding can be alleviated. As a result, molding whitening is also improved, so that the crack resistance caused by the bending stress of the packaging material 20 can be improved. In addition, while maintaining the crystallinity of the modified polyolefin resin component (a) in the first sealant layer 16a, flexibility can be imparted, thereby suppressing the reduction of the bending resistance (crack resistance) of the packaging material 20.
[0175] (Isotactic propylene-α-olefin copolymer (d))
[0176] The resin composition β may further contain an isotactic propylene-α-olefin copolymer (hereinafter simply referred to as “component (d)”) as an additive component in addition to the above-mentioned component (c).
[0177] By further adding component (d) as an additive component to the adhesive resin component as the main component of the resin composition β, flexibility for relieving stress can be imparted, thereby improving heat sealing strength. In addition, by combining component (c) and component (d) as additive components, whitening phenomenon and bending resistance can be further improved.
[0178] In the resin composition β, the total mass of the component (a) and the component (b) may be, for example, 60 mass % to 95 mass % or 80 mass % to 90 mass % based on the total mass of the first sealant layer 16a.
[0179] In the resin composition β, based on the total mass of component (a), component (b), component (c) and component (d), the total mass of component (c) and component (d) is preferably 5% by mass or more and 40% by mass or less. When the total mass of component (a), component (b), component (c) and component (d) is less than 5% by mass, the effect of adding the above-mentioned additives cannot be fully obtained. On the other hand, when the total mass of component (a), component (b), component (c) and component (d) exceeds 40% by mass, the adhesion of the first sealant layer 16a relative to other layers such as the second sealant layer 16b or the anticorrosion treatment layer 14 tends to be easily reduced. From these viewpoints, in the resin composition β, based on the total mass of component (a), component (b), component (c) and component (d), the total mass of component (a) and component (b) is preferably 60 to 95% by mass.
[0180] In addition, the component (c) as an analysis method of the additive component in the resin composition β can be quantified by, for example, evaluating the stereoregularity by nuclear magnetic resonance spectroscopy (NMR).
[0181] On the other hand, as an analysis of component (d), Fourier transform infrared spectroscopy (FT-IR) can be used to draw a calibration curve for the absorber attributed to the branch of α-olefin and the absorber attributed to the characteristic absorber of the modified polyolefin resin (a), thereby confirming the mixing ratio.
[0182] In addition to the adhesive resin composition (i.e., the modified polyolefin resin (a) component and the macro-phase-separated thermoplastic elastomer (b) component) and the additive components (i.e., the components (c) and (d)), the resin composition β may also contain various additives such as flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc. as needed.
[0183] The thickness of the first sealant layer 16 a is not particularly limited, but is preferably the same as or less than that of the second sealant layer 16 b from the viewpoint of stress relaxation and water permeation.
[0184] In addition, in the all-solid battery packaging material 20, from the viewpoint of thin film, the thickness of the sealant layer 16 (the total thickness of the first sealant layer 16a and the second sealant layer 16b) can be 35 μm or less, or 30 μm or less. Even if the all-solid battery packaging material of this embodiment has such a thin film structure, it can suppress the reduction of crack resistance after heat sealing and molding, and can achieve harmlessness to hydrogen sulfide, thereby suppressing corrosion of the collector.
[0185] although Figure 2 FIG. 4 shows a case where the sealant layer 16 is formed of two layers, but Figure 3 As shown in the all-solid battery packaging material 30, the sealant layer 16 may also be formed of three layers. Figure 3 In the all-solid battery packaging material 30 shown, the sealant layer 16 is composed of a first sealant layer 16a, a second sealant layer 16b, and a third sealant layer 16c. Here, the first sealant layer 16a is the outermost layer (metal foil side layer) of the sealant layer, the third sealant layer 16c is the middle layer of the sealant layer, and the second sealant layer 16b is the innermost layer of the sealant layer. At least one layer selected from the group consisting of these three layers is an ionomer-containing layer containing the above-mentioned ionomer.
[0186] Examples and preferred aspects of the material constituting the first sealant layer 16 a of the all-solid-state battery exterior material 30 are the same as those of the first sealant layer 16 a of the all-solid-state battery exterior material 20 .
[0187] Examples and preferred aspects of the materials constituting the second sealant layer 16 b and the third sealant layer 16 c of the all-solid-state battery exterior material 30 are the same as those of the second sealant layer 16 b of the all-solid-state battery exterior material 20 .
[0188] In the packaging material 30 for all-solid-state batteries, the thickness of the first sealant layer 16a can be, for example, 2 to 30 μm, 5 to 20 μm, or 8 to 10 μm, the thickness of the second sealant layer 16b can be, for example, 10 to 80 μm, 13 to 40 μm, or 15 to 20 μm, and the thickness of the third sealant layer 16c can be, for example, 2 to 30 μm, 5 to 20 μm, or 8 to 10 μm.
[0189] In the all-solid battery packaging material 30, from the viewpoint of thin film, the thickness of the sealant layer 16 (the total thickness of the first sealant layer 16a, the second sealant layer 16b, and the third sealant layer 16c) can be 30 μm or less. Even if the all-solid battery packaging material of this embodiment has such a thin film structure, it can suppress the reduction of crack resistance after heat sealing and molding, and can achieve harmlessness to hydrogen sulfide, thereby suppressing corrosion of the collector.
[0190] When the sealant layer 16 is composed of multiple layers as in the all-solid battery packaging materials 20 and 30, the sealant layer 16 may include an ionomer layer composed only of an ionomer and a base resin composition layer containing no ionomer but a base resin composition. Figure 2 In the case of the two-layer structure shown in FIG. 1 , as the laminated structure of the first sealant layer 16a / the second sealant layer 16b, there can be listed a laminated structure of an ionomer single layer / a base resin composition layer, and a laminated structure of a base resin composition layer / an ionomer single layer. Figure 3 In the case of the three-layer structure shown in FIG. 1 , as the laminated structure of the first sealant layer 16a / the third sealant layer 16c / the second sealant layer 16b, there can be listed a laminated structure of an ionomer single layer / a base resin composition layer / an ionomer single layer, and a laminated structure of a base resin composition layer / an ionomer single layer / a base resin composition layer. Among these, from the viewpoint of obtaining better heat sealability, it is preferred that the second sealant layer 16b as the innermost layer is a laminated structure of a base resin composition layer. In addition, from the viewpoint of further improving heat sealability, the ionomer single layer in the above-mentioned laminated structure may be changed to a mixed resin layer, and from the viewpoint of further promoting the harmlessness of hydrogen sulfide, the base resin composition layer in the above-mentioned laminated structure may be changed to a mixed resin layer.
[0191] In addition, Figure 2 and Figure 3 In the all-solid battery packaging materials 20 and 30 shown in FIG. 1 , from the viewpoint of improving the adhesion between the sealant layer 16 and the anti-corrosion treatment layer 14, as shown in FIG. Figure 1 As shown, a second adhesive layer 17 may be provided between the sealant layer 16 and the anti-corrosion treatment layer 14 .
[0192] [Method for producing packaging material]
[0193] Next, Figure 1 An example of a method for manufacturing the sealing material 10 shown in FIG.
[0194] The manufacturing method of the packaging material 10 of the present embodiment is generally composed of: a process of stacking an anti-corrosion treatment layer 14 on a barrier layer 13; a process of pasting a substrate layer 11 and a barrier layer 13 together; a process of further stacking a sealant layer 16 via a second adhesive layer 17 to produce a laminate; and a process of performing an aging treatment on the obtained laminate as needed.
[0195] (Step of Laminating the Anticorrosion Treatment Layer 14 on the Barrier Layer 13)
[0196] This step is a step of forming the anticorrosion treatment layer 14 with respect to the barrier layer 13. As described above, the method thereof includes: performing degreasing treatment, hydrothermal modification treatment, anodizing treatment, chemical conversion treatment, or coating a coating agent having anticorrosion performance on the barrier layer 13.
[0197] In addition, in the case where the anti-corrosion treatment layer 14 is multi-layered, for example, a coating liquid (coating agent) constituting the anti-corrosion treatment layer on the lower side (barrier layer 13 side) can be applied on the barrier layer 13 and fired to form a first layer, and then a coating liquid (coating agent) constituting the anti-corrosion treatment layer on the upper side can be applied on the first layer and fired to form a second layer.
[0198] Degreasing treatment can be carried out by spraying or dipping; hydrothermal modification treatment or anodizing treatment can be carried out by dipping; as for chemical conversion treatment, depending on the type of chemical conversion treatment, dipping, spraying, coating, etc. can be appropriately selected and carried out.
[0199] As for the coating method of the coating agent having an anticorrosive function, various methods such as a gravure coating method, a reverse coating method, a roll coating method, and a bar coating method can be used.
[0200] As described above, various treatments can be applied to both sides or one side of the metal foil, but when a single side is treated, the treatment is preferably applied to the side where the second adhesive layer 17 is laminated. The above treatments can also be applied to the surface of the base layer 11 as needed.
[0201] In addition, the coating amount of the coating agent used to form the first layer and the second layer is preferably 0.005 to 0.200 g / m 2 , more preferably 0.010 to 0.100 g / m2 .
[0202] When drying and curing is required, it can be performed within a range of 60 to 300° C., which is the base material temperature, depending on the drying conditions of the anticorrosion treated layer 14 used.
[0203] (Step of pasting substrate layer 11 and barrier layer 13)
[0204] This step is a step of bonding the barrier layer 13 provided with the anticorrosion treatment layer 14 and the base layer 11 together via the first adhesive layer 12. As a bonding method, dry lamination, solventless lamination, wet lamination or the like can be used to bond the two together using the material constituting the first adhesive layer 12. The dry coating amount of the first adhesive layer 12 is set to 1 to 10 g / m 2 In the range of 3 to 7 g / m 2 within the range.
[0205] (Step of Laminating Second Adhesive Layer 17 and Sealant Layer 16)
[0206] This step is a step of attaching the sealant layer 16 to the anticorrosion treated layer 14 side of the barrier layer 13 via the second adhesive layer 17. Examples of the attaching method include a wet process and a dry lamination method.
[0207] In the case of a wet process, a solution or dispersion of an adhesive constituting the second adhesive layer 17 is applied to the anti-corrosion treatment layer 14, and the solvent is removed at a predetermined temperature (a temperature above the melting point of an acid-modified polyolefin resin in the case of the adhesive) to dry the film, or a firing process is performed after drying the film as required. Then, the sealant layer 16 is laminated to manufacture the packaging material 10. As the coating method, various coating methods exemplified above can be cited.
[0208] (Aging treatment process)
[0209] This process is a process of performing an aging (curing) treatment on the laminate. By performing an aging treatment on the laminate, the adhesion between the barrier layer 13 / the anti-corrosion treatment layer 14 / the second adhesive layer 17 / the sealant layer 16 can be promoted. The aging treatment can be performed in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days. In addition, in order to achieve adhesion between the second adhesive layer 17 / the sealant layer 16, a heat treatment can be performed at a temperature above the melting point of the second adhesive layer 17. As heat treatments, methods such as oven heating, clamping with heated rollers (hot lamination), and winding on heated rollers can be listed, but are not limited to these.
[0210] Thus, it is possible to produce Figure 1The packaging material 10 of the present embodiment is shown.
[0211] Next, Figure 2 An example of a method for manufacturing the sealing material 20 shown in FIG.
[0212] The manufacturing method of the packaging material 20 of this embodiment generally includes: a step of laminating the anti-corrosion treatment layer 14 on the barrier layer 13; a step of pasting the base layer 11 and the barrier layer 13 together; a step of further laminating the first sealant layer 16a and the second sealant layer 16b to produce a laminate; and a step of heat-treating the obtained laminate as required. It should be noted that the steps until pasting the base layer 11 and the barrier layer 13 together can be performed in the same manner as the manufacturing method of the packaging material 10 described above.
[0213] (Step of Laminating First Sealing Agent Layer 16a and Second Sealing Agent Layer 16b)
[0214] This process is a process for forming the first sealant layer 16a and the second sealant layer 16b on the anticorrosion treatment layer 14 formed by the previous process. As its method, a method for sandwich laminating the first sealant layer 16a and the second sealant layer 16b using an extrusion laminating machine can be cited. In addition, the first sealant layer 16a and the second sealant layer 16b can also be laminated by a double extrusion lamination method or a coextrusion method. The resin composition used for the formation of the first sealant layer 16a and the resin composition used for the formation of the second sealant layer 16b can be prepared by mixing each component in a manner that satisfies the composition of the first sealant layer 16a and the second sealant layer 16b.
[0215] Through this process, we can obtain Figure 2 The laminate shown is a laminate in which the following layers are laminated in this order: base material layer 11 / first adhesive layer 12 / barrier layer 13 / anticorrosion treatment layer 14 / first sealant layer 16 a / second sealant layer 16 b .
[0216] It should be noted that the first sealant layer 16a can be directly laminated with the dried mixed materials using an extrusion laminator to make it a mixed composition of the above materials, or it can be preliminarily melt-mixed using a single-screw extruder, a twin-screw extruder, a Brabender mixer or other melt-kneading device to obtain granules, and the granulated first sealant layer 16a can be laminated using an extrusion laminator.
[0217] The second sealant layer 16b can be directly laminated with the dried mixed materials using an extrusion laminator to form the above-mentioned material mixture composition as the resin composition for forming the sealant layer, or it can be melt-mixed in advance using a single-screw extruder, a twin-screw extruder, a Brabender mixer or other melt-kneading device to obtain granules, and the first sealant layer 16a and the second sealant layer 16b can be laminated using an extrusion laminator by a double extrusion lamination method or a coextrusion method. In addition, the resin composition for forming the sealant layer can be used to prepare a single sealant film as a casting film in advance, and the film can be laminated together with an adhesive resin using a sandwich lamination method, or the film can be laminated using a dry lamination method and an adhesive.
[0218] (Heat treatment process)
[0219] This step is a step of heat treating the laminate. By heat treating the laminate, the adhesion between the barrier layer 13 / the anticorrosion treatment layer 14 / the first sealant layer 16a / the second sealant layer 16b can be improved. As a method of heat treatment, it is preferred to treat at a temperature at least above the melting point of the first sealant layer 16a.
[0220] Thus, it is possible to produce Figure 2 The packaging material 20 of this embodiment is shown.
[0221] Next, Figure 3 An example of a method for manufacturing the sealing material 30 shown in FIG.
[0222] The manufacturing method of the packaging material 30 of the present embodiment is generally composed of: a process of stacking the anti-corrosion treatment layer 14 on the barrier layer 13; a process of pasting the substrate layer 11 and the barrier layer 13 together; a process of further stacking the first sealant layer 16a, the third sealant layer 16c, and the second sealant layer 16b to make a stack; and a process of heat treating the obtained stack as needed.
[0223] (Step of Laminating First Sealing Agent Layer 16a, Third Sealing Agent Layer 16c, and Second Sealing Agent Layer 16b)
[0224] This process is a process for forming the first sealant layer 16a, the third sealant layer 16c and the second sealant layer 16b on the anticorrosion treatment layer 14. As the method, there can be listed: a co-layering method and a co-extrusion method in which the first sealant layer 16a, the third sealant layer 16c and the second sealant layer 16b are extruded by an extrusion laminating machine. In this case, the dried mixed material can be directly laminated by an extrusion laminating machine to form a mixed composition of the above-mentioned materials as a resin composition for forming the sealant layer, or a melt kneading device such as a single-axis extruder, a double-axis extruder, a Brabender mixer, etc. can be used in advance to implement melt mixing to obtain granules, and the first sealant layer 16a, the third sealant layer 16c and the second sealant layer 16b are laminated by a double extrusion laminating method or a co-extrusion method using an extrusion laminating machine.
[0225] The third sealant layer 16 c and the second sealant layer 16 b can be formed into films by co-extrusion, and these films can be laminated together with the resin composition for forming the first sealant layer 16 a by sandwich lamination.
[0226] Thus, it is possible to produce Figure 3 The packaging material 30 of the present embodiment is shown.
[0227] The preferred embodiments of the all-solid battery packaging material of the present invention are described in detail above, but the present invention is not limited to these specific embodiments, but various deformations and changes can be made within the scope of the gist of the present invention described in the claims. For example, in the case of manufacturing an all-solid battery packaging material without the first adhesive layer 12, as described above, the substrate layer 11 can be formed by coating or applying a resin material that can form the substrate layer 11 on the barrier layer 13.
[0228] [All-solid-state battery]
[0229] Figure 4 1 is a perspective view showing an embodiment of a fully solid-state battery manufactured using the above-mentioned packaging material. Figure 4As shown, the all-solid-state battery 50 is constructed to include: a battery element 52, two metal terminals (current output terminals) 53 for outputting current from the battery element 52 to the outside, and a packaging material 10 that contains the battery element 52 in an airtight state. The packaging material 10 is the packaging material 10 involved in the above-mentioned present embodiment. In the packaging material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, with respect to the packaging material 10, in a manner such that the base material layer 11 becomes the outer side of the all-solid-state battery 50 and the sealant layer 16 becomes the inner side of the all-solid-state battery 50, by folding one laminated film in half and heat-melting it, or by overlapping two laminated films and heat-melting them, a structure containing the battery element 52 inside is formed. It should be noted that in the all-solid-state battery 50, the packaging material 20 or the packaging material 30 can also be used instead of the packaging material 10.
[0230] The battery element 52 is formed by sandwiching a sulfide-based solid electrolyte between a positive electrode and a negative electrode. The metal terminal 53 is formed by a part of the collector extending to the outside of the packaging material 10, and is composed of a metal foil such as copper foil or aluminum foil. In the all-solid-state battery 50 of this embodiment, even if the battery element 52 generates hydrogen sulfide, the hydrogen sulfide can be detoxified by the packaging material 10, so that the corrosion of the metal terminal (collector) 53 inside the packaging material 10 can be suppressed, and even if the packaging material 10 is damaged, the leakage of hydrogen sulfide to the outside can be suppressed, thereby ensuring excellent safety.
[0231] Example
[0232] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the following examples.
[0233] [Materials used]
[0234] The materials used in Examples and Comparative Examples are as follows.
[0235] <Base layer (thickness 15 μm)>
[0236] A nylon (Ny) film (manufactured by Toyobo Co., Ltd.) was used.
[0237] <First Adhesive Layer (Thickness 4 μm)>
[0238] A polyurethane adhesive (manufactured by "Toyo Ink Co., Ltd.") was used in which a polyester polyol-based main agent was mixed with an adduct-based curing agent of toluene diisocyanate.
[0239] <First Anticorrosion Treatment Layer (Base Layer Side) and Second Anticorrosion Treatment Layer (Sealing Agent Layer Side)>
[0240] (CL-1): "Sodium polyphosphate stabilized cerium oxide sol" using distilled water as a solvent and adjusted to a solid content concentration of 10 mass %. The sodium polyphosphate stabilized cerium oxide sol is obtained by mixing 10 mass parts of sodium phosphate with 100 mass parts of cerium oxide.
[0241] (CL-2): A composition composed of 90% by mass of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corp.)" adjusted to a solid content concentration of 5% by mass using distilled water as a solvent.
[0242] <Barrier layer (thickness 35 μm)>
[0243] An annealed and degreased soft aluminum foil ("8079 material" manufactured by "Toyo Aluminum KK") was used.
[0244] <Second Adhesive Layer (Thickness 3 μm)>
[0245] As the adhesive for forming the second adhesive layer, the following adhesives a and b were prepared.
[0246] Adhesive a: An adhesive prepared by mixing 10 parts by mass (solid content ratio) of a polyisocyanate compound having an isocyanurate structure with 100 parts by mass of an acid-modified polyolefin resin dissolved in toluene.
[0247] Adhesive b: A polyurethane-based adhesive obtained by mixing polyester polyol composed of a hydrogenated dimer fatty acid and a diol with polyisocyanate so that the molar ratio (NCO / OH) becomes 2.
[0248] <Sealing agent layer>
[0249] [Resin composition for forming sealant layer]
[0250] As constituent materials of the sealant layer-forming resin composition, the following base resin, compatible elastomer, ionomer, LDPE, and compatibilizers a and b were prepared. These materials were mixed in the mass ratio shown in Table 1 to prepare a sealant layer-forming resin composition.
[0251] Base resin: Propylene-ethylene random copolymer (random PP).
[0252] Compatible elastomer: A propylene-butene-1 random copolymer elastomer (propylene-butene-1) having compatibility with the base resin.
[0253] Ionomer: An ionomer resin formed by cross-linking the molecules of ethylene-α,β-unsaturated carboxylic acid copolymer using zinc ions.
[0254] LDPE: low-density polyethylene (manufactured by "Japan Polyethylene Corporation", "LC600A").
[0255] Compatibilizer a: a block copolymer composed of propylene units and ethylene units.
[0256] Compatibilizer b: a block copolymer composed of crystalline ethylene units and ethylene-butene units.
[0257] [Examples 1 to 13 and Comparative Examples 1 to 3]
[0258] First, the first and second anticorrosion treatment layers were formed on the barrier layer in the following manner. That is, (CL-1) was applied by micro gravure coating at a dry coating amount of 70 mg / m 2 The barrier layer was coated on both sides of the barrier layer and fired at 200°C in a drying unit. Then, (CL-2) was coated with a dry coating amount of 20 mg / m by micro gravure coating. 2 The first and second anti-corrosion treatment layers are formed by coating the obtained layer with (CL-1) and (CL-2) in a manner to form a composite layer composed of (CL-1) and (CL-2). The composite layer exhibits anti-corrosion performance by combining the two substances (CL-1) and (CL-2).
[0259] Next, the first anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers was adhered to the base material layer using a polyurethane adhesive (first adhesive layer) by dry lamination. Next, the second anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers was adhered to the sealant layer (thickness 30 μm) formed in advance as a cast film by dry lamination using adhesive a or b (second adhesive layer) shown in Table 1. In forming the sealant layer, a resin composition for forming a sealant layer having a composition shown in Table 1 was used.
[0260] The laminate obtained as described above was subjected to aging treatment at 40°C for 4 days to produce the packaging material of Example 7 (laminate of substrate layer / first adhesive layer / first anticorrosion treatment layer / barrier layer / second anticorrosion treatment layer / second adhesive layer / sealant layer).
[0261] [Example 14]
[0262] As in Example 1, the first and second anti-corrosion treatment layers are provided on the barrier layer. The first anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers is adhered to the substrate layer using a polyurethane-based adhesive (first adhesive layer) by dry lamination. The sealant layer (thickness 30 μm) is laminated on the second anti-corrosion treatment layer by placing it in the unwinding section of an extrusion laminator and co-extruded the material of the sealant layer under processing conditions of 290°C and 100 m / min. It should be noted that the sealant layer is a composite of various materials prepared in advance using a twin-shaft extruder, and is subjected to a water cooling / granulation process for the above-mentioned extrusion lamination. In the formation of the sealant layer, a resin composition for forming a sealant layer having the composition shown in Table 1 is used.
[0263] The stacked body obtained as described above is heat treated so that the maximum temperature reached by the stacked body becomes 190°C, thereby producing the packaging material of Example 14 (a stacked body of substrate layer / first adhesive layer / first anti-corrosion treatment layer / barrier layer / second anti-corrosion treatment layer / sealant layer).
[0264] [Example 15]
[0265] As in Example 1, the first and second anti-corrosion treatment layers are provided on the barrier layer. The first anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers is adhered to the substrate layer using a polyurethane-based adhesive (first adhesive layer) by dry lamination. Next, the second anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers is adhered to a sealant layer (thickness 30 μm) previously formed as a cast film using adhesive a (second adhesive layer) by dry lamination. The sealant layer is a laminated film formed by co-extruding two sealant layer-forming resin compositions having the compositions shown in Table 2 to form a layer on the metal foil side (hereinafter also referred to as the "AL side layer") (thickness 15 μm) and an innermost layer (thickness 15 μm).
[0266] [Example 16]
[0267] As in Example 1, the first and second anti-corrosion treatment layers are provided on the barrier layer. The first anti-corrosion treatment layer side of the barrier layer provided with the first and second anti-corrosion treatment layers is adhered to the substrate layer using a polyurethane adhesive (first adhesive layer) by dry lamination. By placing it in the unwinding section of an extrusion laminating machine and co-extruded the material of the sealant layer under processing conditions of 290°C and 100 m / min, a layer on the metal foil side of the sealant layer (hereinafter also referred to as "AL side layer") (thickness 15 μm) and an innermost layer (thickness 15 μm) are sequentially laminated on the second anti-corrosion treatment layer. It should be noted that the AL side layer and the innermost layer are composites of various materials prepared in advance using a twin-screw extruder, and are subjected to a water cooling / granulation process for the above-mentioned extrusion lamination. In the formation of the AL side layer and the innermost layer, a resin composition for forming a sealant layer having the composition shown in Table 2 is used.
[0268] The stacked body obtained as described above is heat treated so that the maximum temperature reached by the stacked body becomes 190°C, thereby producing the packaging material of Example 16 (a stacked body of substrate layer / first adhesive layer / first anti-corrosion treatment layer / barrier layer / second anti-corrosion treatment layer / sealant layer (AL side layer) / sealant layer (innermost layer)).
[0269] [Table 1]
[0270]
[0271] [Table 2]
[0272]
[0273] <Evaluation>
[0274] The packaging materials obtained in Examples and Comparative Examples were subjected to the following evaluation tests.
[0275] (Heat seal strength)
[0276] The packaging material was cut into 60 mm × 120 mm samples, folded in half, and heat-sealed on one side using a 10 mm wide sealing strip at 190°C, 0.5 MPa, and 3 seconds. After the heat-sealed packaging material was stored at room temperature (25°C) for 24 hours, the heat-sealed portion was cut into 15 mm wide pieces (refer to Figure 5 ), and the sealing strength (T-peel strength) was measured using a testing machine (manufactured by INSTRON). According to JIS K6854, the test was conducted at a peeling speed of 50 mm / min in an atmosphere of 23°C and 50% RH. The measurement results are shown in Table 3. A sealing strength of 30 N / 15 mm or more was considered acceptable.
[0277] (Corrosion Evaluation)
[0278] The packaging material was cut into a sample 40 of 120 mm × 200 mm, and placed on a cold forming die so that the sealant layer was in contact with the convex portion of the forming machine, and a 2.0 mm punch was performed at a forming speed of 15 mm / sec to form a punched portion 41, which was then folded in half to 120 mm × 100 mm (refer to Figure 6 (a)). The die used had a molding area of 80 mm × 70 mm (square tube type) and a punch corner radius (RCP) of 1.0 mm. Next, the upper edge 44 of 100 mm was heat-sealed (see Figure 6 (b)), and then heat-sealed the 120 mm side edge 45 to form a bag (refer to Figure 6 (c)). Then, 5 ml of 1 mass ppm hydrogen sulfide gas (refer to Figure 6 (d)), and heat seal the lower edge 46 of 100 mm (refer to Figure 6 (e)). Then, the bag was stored in a thermostatic chamber at 40°C for 1 month, and the corrosion condition of the copper foil tab 42 inside the bag after opening was visually confirmed. The case where any of discoloration, spots, rust, and dendrites occurred on the copper foil tab 42 was judged as "B" (corrosion); the case where none of these occurred was judged as "A" (no corrosion). The results are shown in Table 3.
[0279] [Table 3]
[0280] Sealing strength (N / 15mm) Copper foil corrosion Example 1 40 A Example 2 39 A Example 3 35 A Example 4 33 A Example 5 45 A Example 6 41 A Example 7 44 A Example 8 41 A Example 9 43 A Example 10 40 A Embodiment 11 42 A Example 12 40 A Example 13 31 A Embodiment 14 30 A Embodiment 15 30 A Example 16 32 A Comparative Example 1 42 B Comparative Example 2 32 B Comparative Example 3 40 B
[0281] Explanation of symbols
[0282] 10, 20, 30…packaging material for all-solid-state battery, 11…substrate layer, 12…first adhesive layer, 13…barrier layer, 14…corrosion protection layer, 16…sealant layer, 16a…first sealant layer, 16b…second sealant layer, 16c…third sealant layer, 17…second adhesive layer, 40…sample, 41…stamping portion, 42…copper foil tab, 43…tab seal, 44…upper edge, 45…side edge, 46…lower edge, 50…all-solid-state battery, 52…battery element, 53…metal terminal.
Claims
1. A packaging material for an all-solid-state battery, which is a packaging material for an all-solid-state battery containing a sulfide-based solid electrolyte, comprising at least: a substrate layer, a barrier layer, and a sealant layer in order, The sealant layer includes a mixed resin layer composed of a polypropylene resin and an ethylene ionomer resin which is an ionomer incompatible with the polypropylene resin. The polypropylene resin is composed of 60 to 95% by mass of a propylene-ethylene random copolymer and 5 to 40% by mass of a compatible polyolefin elastomer having a melting point of 150° C. or less and containing butene-1 as a comonomer.
2. The all-solid battery packaging material according to claim 1, wherein: The metal ions forming the ionomer include zinc ions.
3. The all-solid battery packaging material according to claim 1 or 2, wherein: The mixed resin layer further contains a compatibilizer having a portion compatible with the polypropylene-based resin and a portion compatible with the ethylene-based ionomer resin.
4. The all-solid battery packaging material according to claim 1 or claim 3, wherein: The content of the ionomer in the mixed resin layer is 1 to 40% by mass based on the total solid content of the mixed resin layer.
5. The all-solid battery packaging material according to any one of claims 1 to 4, wherein: The sealant layer is composed of a plurality of layers, at least one layer of which is a layer containing the ionomer, and at least one other layer is a layer containing a polypropylene-based resin.
6. The all-solid battery packaging material according to any one of claims 1 to 5, wherein: An anti-corrosion treatment layer is provided on one or both surfaces of the barrier layer.
7. The all-solid battery packaging material according to claim 6, wherein: The anticorrosion treatment layer contains cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate based on 100 parts by mass of the cerium oxide, and a cationic polymer.
8. An all-solid-state battery comprising: A battery element containing a sulfide-based solid electrolyte, a current output terminal extending from the battery element, and The packaging material for a solid-state battery according to any one of claims 1 to 7, which holds the current output terminal and accommodates the battery element.
Citation Information
Patent Citations
All-solid battery
JP2008103283A
All-solid battery
JP2008103288A